Malnutrition and it’s consequences among University Malaysia Kelantan city campus students: The qualitative analysis - Nor Aziean Alias; Nor Faznina Hashim; Muhammad Haris Danial Sawani@Saidulahad; Seek Zhi Wei (2022)
This study is conducted to determine the link between mental health and malnutrition among University Malaysia Kelantan city campus students. The main purpose this research is to investigate the link between a lack of knowledge and malnutrition among University Malaysia Kelantan City Campus students. The qualitative analysis approach is chosen and the data collection method that used is a personal semi-structured interview which is open-ended questionnaire by distributing it through platform social media which is WhatsApp, Facebook, Instagram and so on. The primary source of data is employed in the data collection method for this research. Using the purposive or judgemental sampling, around 30 students have conducted a personal semi-structured interview and 20 students have conducted an online survey which is questionnaire. That way very easy to be distributed and collect data information from respondent. Total of a respondent is around 50 students conducted in a personal semi-structured interview and also online survey like questionnaire. In this study, the data are analysed by thematic analysis. Hence this study can help other researcher in the future when they want to investigate the link between a lack of knowledge and malnutrition among University Malaysia Kelantan City Campus students.